(untitled) (Research, Society and Development, 2021)
The present article aims to discuss about the functionality of mediation and arbitration as alternative instruments for solving potential controversies in conflicts of interests from the business sector of agribusiness, focusing on the values and prices of the contracts between private entities, where the emphasis is to harmonize common interests as well as the private ones, by solving contractual and economic issues, through faster, de-bureaucratic and effective procedures, in the sense to produce decisions closest to the personalities of the interested ones, also collaborating with the reduction of the judicialization of cases, using a methodological construction of bibliographical researches, with revisions of the legislations, doctrines and jurisprudence recently developed, in a quantitative and descriptive procedure of concepts and results, contextualizing contract models of this industrial sector, which is traditionally close to governments, international legislations and huge amount of financial concentration. The results show that, in the face of conflicting international legislation, mediation and arbitration are the most beneficial methods for harmonizing the parties’ interests in contracts.